Symbolic Convergence and Fantasy Themes in Community-Based Ecotourism Communication: A Case Study of Pokdarwis Situ Gede - Faris Budiman Annas; Djuara P Lubis; Dwi Retno Hapsari; Sumardjo (INJECT (Interdisciplinary Journal of Communication), 2025)
Situ Gede is an ecotourism destination in Bogor City that combines the attractions of a lake ecosystem and a forest. Situ Gede ecotourism is a community-based ecotourism site managed by the Local Kelompok Sadar Wisata (Pokdarwis) Situ Gede. Communication interactions within Pokdarwis generate various fantasy themes, which then form symbolic convergence (Bormann, Cragan, & Shields, 2001). These fantasy themes flow through both offline and online communication via WhatsApp group. This research aims to understand how the fantasy themes formed within Pokdarwis Situ Gede relate to the principles of ecotourism development. This study is qualitative, employing several methods, including virtual ethnography, observation, and interviews. The findings reveal that the rhetorical vision of Pokdarwis Situ Gede can be divided into four pillars: environmental education, conservation, community empowerment, and livelihood enhancement.